PICOSECOND DISTRIBUTED FEEDBACK LASER IN INFRARED -VISIBLE SPECTRAL RANGE - Lalayan, A. A.
A novel scheme of the picosecond DFB dye laser with a wide tuning range of 2900 Å in the visible-infrared range has been realized. Influence of the pumping pulse energy on DFB laser output temporal properties has been investigated numerically and the shortening of the first generated pulses with the increasing of pump energy has been demonstrated.
Keywords: Physics; Instruments, apparatus, components common to several branches of physics; Optics